KELOMPOK SWADAYA MASYARAKAT (KSM ) JELITA KAMPUNG SANTREN GADINGKASRI KECAMATAN KLOJEN MALANG - Dewi Nurjannah; Sri Nastiti Andarini (Bajang Institute, 2025)
This Community Service program is a continuation of previous community service programs, gradually realizing an Islamic-themed village with a 5D concept: what can be seen, enjoyed, lived in, studied, and brought home (as souvenirs) from the Santren village. The partner in this Community Service program is the Community Self-Help Group (KSM Jelita), which was formed during the previous Community Service program. KSM Jelita is a community group whose members have businesses that, although relatively small, can contribute to the family's income. These include a cigarette stall, making rempeyek (crackers) sold in nearby shops, selling ice, and accepting orders for boxed meals. To support the development of the thematic village, KSM Jelita is also preparing to make souvenirs and improve its skills. The established Self-Help Group has also added a culture and creativity section to its organizational structure, while also supporting the thematic village program for the Santren village to raise awareness about tourism.